Evaluation of a new stent for EUS-guided pancreatic duct drainage: long-term follow-up outcome - Matsunami, Yukitoshi; Itoi, Takao; Sofuni, Atsushi; Tsuchiya, Takayoshi; Kamada, Kentaro; Tanaka, Reina; Tonozuka, Ryosuke; Honjo, Mitsuyoshi; Mukai, Shuntaro; Fujita, Mitsuru; Yamamoto, Kenjiro; Asai, Yasutsugu; Kurosawa, Takashi; Tachibana, Shingo; Nagakawa, Yuichi (Endoscopy International Open, 2018)
Background and study aims Endoscopic ultrasonography-guided pancreatic duct drainage (EUS-PD) has been reported as an alternative for failed conventional endoscopic retrograde cholangiopancreatography (ERCP). However, there are few dedicated devices for EUS-PD. Recently, we have developed a new plastic stent dedicated to EUS-PD and have conducted a feasibility study to evaluate its efficacy. In the current study, we evaluated the long-term efficacy of this new plastic stent.Patients and methods Thirty patients (61 ± 14.3 years old, 14 men) with acute recurrent pancreatitis caused by a stricture in the main pancreatic duct (MPD) or stenotic pancreatoenterostomy were treated at our institution using our recently developed 7Fr plastic stent between August 2013 and April 2017.Results The stent was placed successfully in all patients (30/30) and early clinical success was achieved in all of them. Early adverse events (AEs) occurred in seven patients (23.3 %), namely, self-limited abdominal pain (n = 5), mild pancreatitis (n = 1), and bleeding which required transcatheter arterial embolization (n = 1). Two patients died of primary disease and three were lost to follow-up. The remaining 25 patients were followed up after initial EUS-PD for a median of 23 months (range, 6 – 44 months). Twenty patients required regular stent exchange (3 times; range, 1 – 12 times). Spontaneous stent dislodgement was observed in six patients. Four patients wanted their stents removed 1 year after the initial intervention. Twelve patients (48 %) had regular stent exchange 1 year after the initial intervention. Three patients converted to standard transpapillary pancreatic duct stenting by conventional ERCP. Finally, nine patients (36 %) had complete stent removal either intentionally or by spontaneous dislodgement without any symptoms.Conclusion The new plastic stent for EUS-PD was associated with not only short-term technical success but also long-term clinical success in the majority of patients evaluated in this study.